2017
DOI: 10.22516/25007440.115
|View full text |Cite
|
Sign up to set email alerts
|

Efectos adversos a largo plazo de los inhibidores de la bomba de protones. Perspectiva desde la medicina basada en la evidencia

Abstract: ResumenLos inhibidores de la bomba de protones (IBP) son los supresores de la secreción gástrica más efectivos y se encuentran entre los medicamentos de mayor formulación y venta en Estados Unidos; en algunos casos son prescritos sin indicación justificada. En años recientes, el reporte de reacciones adversas importantes relacionadas con su uso ha suscitado preocupación. Sin embargo, la calidad de la evidencia no ha sido concluyente y, en algunos casos, la magnitud del riesgo no es de importancia clínica. El o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 28 publications
0
21
0
3
Order By: Relevance
“…37,38 However, given the presence of proton pumps in osteoclasts, a reduction in bone resorption due to an inhibitory effect of the drug is also possible. 38 The meta-analysis by Kwok et al confirmed that there was an increased risk of fracture, especially in the lumbar spine, after using PPIs. 39 van der Hoorn et al, in a cohort study of elderly Australian women, documented elevated risks of osteoporosis (adjusted subhazard ratio [SHR]: 1.28, 95% CI: 1.13-1.44) and fracture (SHR: 1.29, 95% CI: 1.08-1.55), mainly with esomeprazole and rabeprazole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 However, given the presence of proton pumps in osteoclasts, a reduction in bone resorption due to an inhibitory effect of the drug is also possible. 38 The meta-analysis by Kwok et al confirmed that there was an increased risk of fracture, especially in the lumbar spine, after using PPIs. 39 van der Hoorn et al, in a cohort study of elderly Australian women, documented elevated risks of osteoporosis (adjusted subhazard ratio [SHR]: 1.28, 95% CI: 1.13-1.44) and fracture (SHR: 1.29, 95% CI: 1.08-1.55), mainly with esomeprazole and rabeprazole.…”
Section: Discussionmentioning
confidence: 99%
“…Proton pump inhibitors were associated with an increased risk of hip fracture in this population, which is concerning, as these drugs are among the most widely prescribed worldwide, with increasing evidence of their potentially deleterious effects on bone due to altered gastric acidity and prevention of the correct ionization and absorption of Ca 2+ , which may lead to hypocalcemia and secondary hyperparathyroidism. 37,38 However, given the presence of proton pumps in osteoclasts, a reduction in bone resorption due to an inhibitory effect of the drug is also possible. 38 The meta-analysis by Kwok et al confirmed that there was an increased risk of fracture, especially in the lumbar spine, after using PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…Cardona Ospina et al 20 show a possible higher risk for enteric infections (Salmonella spp., Campylobacter jejuni, Escherichia coli, Clostridium difficile, Vibrio cholerae and Listeria spp.) 21 with the use of PPIs (especially CDI), despite heterogeneity between outcomes and variable interactions such as antibiotic use.…”
Section: Enteric Infectionsmentioning
confidence: 99%
“…PPIs modify chloride acid production by irreversibly inhibiting H/K-ATPase on parietal cells. 2 There are currently five PPI drugs commercially available: omeprazole, esomeprazole, lansoprazole, pantoprazole, and rabeprazole, which have very similar pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%